Alan R. H. Baker & Gideon Biger (eds.): Ideology and Landscape in Historical Perspective - Olwig, Kenneth R. (Tidsskriftet Antropologi, 1993)
Alan R. H. Baker & Gideon Biger (eds.): Ideology and Landscape in Historical Perspective Anmeldes af Kenneth R. Olwig